Techno‐economic studies on the influences of nonuniform feeding in the biogas plants of educational institutions. Issue 6 (4th May 2018) - Glivin, Godwin; Edwin, M.; Sekhar, S. Joseph
Abstract : The scarcity of conventional energy sources and their environmental impacts have led to successful implementation of biogas technologies in various applications. However, the lack of awareness in the society and economic viability are a few constraints that hinder the effective use of biogas in many sectors. Therefore, intensive research is needed to overcome the above said issues and extend the use of biogas into many newer avenues. Academic institutions are the places where people have more awareness on the environmental impacts. However, the nonuniform availability of biowastes and the lack of studies on the economic benefits of this technology restrict the implementation of the same. This study focuses on the economic benefits of implementing three types of biogas digesters, KVIC, JANATA, and Fiber‐glass reinforced polyester biogas plants, in five different academic institutions where the student population and generation of biowastes throughout a year are nonuniform, and the digester may not run with full load continuously. Based on a pilot study, the quality and quantity variations because of the nonuniform strength of student during a year have been studied and the same have been used to predict the biogas generation in the selected institutions. The result shows that biogas energy production is economically viable for capacities ranging from 25 to 450 m 3 with a payback period between 3.18 and 7.59 years for various types used in the study. The economic viability of the biogas plants is proved with positive net present value. © 2018 American Institute of Chemical Engineers Environ Prog, 37: 1901–1907, 2018